Blood Glucose Monitoring Biosensor Based on Multiband Split-Ring Resonator Monopole Antenna - Dalia N. Elsheakh; EL-Hawary Mohamed; Angie R. Eldamak (Biosensors)
This paper introduces a novel-shaped, compact, multiband monopole antenna sensor incorporating an irregular curved split-ring resonator (SRR) design for non-invasive, continuous monitoring of human blood glucose levels (BGL). The sensor operates at multiple resonance frequencies: 0.94, 1.5, 3, 4.6, and 6.3 GHz, achieving coefficient reflection impedance bandwidths ≤ −10 dB of 4%, 1%, 3.5%, 65%, and 50%, respectively. Additionally, novel shapes of two SRR metamaterial cells create notches at 1.7 GHz and 4.4 GHz. The antenna is fabricated on an economical FR4 substrate with compact dimensions of 35 × 50 × 1.6 mm3. The sensor’s performance is evaluated using 3D electromagnetic software, incorporating a human finger phantom model and applying the Cole–Cole model to mimic the blood layer’s sensitivity to blood glucose variations. The phantom model is positioned at different angles relative to the biosensor to detect frequency shifts corresponding to different glucose levels. Experimental validation involves placing a real human finger around the sensor to measure resonant frequency, magnitude, and phase changes. The fabricated sensor demonstrates a superior sensitivity of 24 MHz/mg/dL effectiveness compared to existing methods. This emphasizes its potential for practical, non-invasive glucose monitoring applications.